Comparative genomics plastomes of the Amaryllidaceae family species - Jimenez, Horace José; Francisco da Silva, Allan Deyws; Semen Martins, Luiza Suely; de Carvalho, Reginaldo; De Moraes Filho, Rômulo Maciel (Scientia Plena, 2020)
The genus Allium covers more than 800 species, signaling among the largest among monocotyledons. The genus contains many economically important species, including garlic, leeks, onions, chives and Chinese chives. Due to the high conservation of chloroplast genomes compared to nuclear genomes and mitochondrial genome, sequence of chloroplasts in Amaryllidaceae have been consistently used for species identification and various in silico programs and strategies have been used to identify, characterize and compare plastid genome regions. Plastome from 15 species of the Amaryllidaceae family revealed similarity in both sequences and in the organization of their gene regions. The base pairs (bp) number ranged from 145,819 (A. paradoxum) to 159,125 (A. ursinum). In respect the GC content, the species presented a variation between 36.7% (A. schoenoprasum and A. sativum) and 37.5% (A. coddii) and the gene space ranged from 84.760 (A. paradoxum) to 94.766 (A. sativum). The genes that encode proteins showed values between 78 (A. paradoxum) to 89 (A. cepa). Phylogenetic trees acquired through alignment of complete plastomas and the plastidial matK gene revealed similarity to the proposed classification for the family. For the genus Allium, there was the formation of three clades with perfect correspondence of the clusters to the three evolutionary lines of the genus.